1995
DOI: 10.1108/00242539510089750
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the reading habits of secondary school students

Abstract: Surveys factors affecting the reading habits of secondary school students in Ogbomoso State in Nigeria and discusses the results. Highlights the following inhibiting factors: the family background of students where few homes are conducive to reading owing to noise and lack of reading materials; the lack of functional libraries in most of the schools surveyed and a similar lack of trained librarians or teacher librarians; the failure to provide library periods in schools; language teachers and shortage of equip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 0 publications
1
21
0
1
Order By: Relevance
“…As in the meaning and definition of reading, the reading objectives differ according to socio-economic and cultural structures of societies. Onwubiko deals with reading objectives in four main topics (Ogunrombi & Adio, 1995):…”
Section: Reading and Reading Habitsmentioning
confidence: 99%
See 2 more Smart Citations
“…As in the meaning and definition of reading, the reading objectives differ according to socio-economic and cultural structures of societies. Onwubiko deals with reading objectives in four main topics (Ogunrombi & Adio, 1995):…”
Section: Reading and Reading Habitsmentioning
confidence: 99%
“…In particular, parents who are encouraging children to look at picture books and reading stories aloud will help them acquire this habit (Yılmaz, 1993). Ogunrombi and Adio (1995) reported that only a few of the families had a library in their studies on the factors affecting the students' reading habits. The authors emphasized the need to have a library at home to support children's education at school.…”
Section: Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Students were also aware of and articulated the value of having a library. Ogunrombi and Adio (1995) found that having functional libraries was a critical factor in development of good reading skills for secondary students in Nigeria. "The acquisition of good reading habits depends largely on the availability of the right type of books.…”
Section: Secondary School Students and Library Usementioning
confidence: 99%
“…Unfortunately, there is at the moment in Nigeria an acute shortage of suitable reading materials for students beginning to read, especially in Nigerian languages" (Ogunrombi & Adio, 1995, 56) The researchers found that in most of the schools they surveyed in Nigeria, there were no libraries and no librarians (Ogunrombi & Adio, 1995). They also discovered that for the few schools that did have libraries, they were often times limited to only senior secondary school students (Ogunrombi & Adio, 1995). The authors concluded that "functional libraries should be established in Nigerian schools" (Ogunrombi & Adio, 1995, 56).…”
Section: Secondary School Students and Library Usementioning
confidence: 99%